Rethinking school leadership for equity, diversity and social justice in education: the case of Northern Cyprus - Küçükakın, Pınar Mercan; Gökmenoğlu, Tuba (International journal of leadership in education, 2023)
A growing body of research highlights the importance of school leadership to create an equitable and inclusive learning environment for students from different backgrounds. The present study explores the role of school leadership in creating an inclusive learning environment and providing a more equitable educational experience for immigrant students in the Northern Cyprus (NC) context. In the last two decades, schools in NC have faced challenges due to increasing numbers of immigrant students. This study is designed as a phenomenological qualitative inquiry, and we interviewed 10 school principals working at elementary schools in NC. Our interviews showed that the leadership abilities of school principals play a vital role in celebrating diversity and ensuring social justice in education. Our analysis points to the needs of school leaders in increasing their agency and capacity to compensate for inequalities that immigrant students face in the NC context.